IPTV video personalized recommendation system - Hongyong YU; Chenxu QIU; Jianfeng WEN (Dianxin kexue)
The personalized recommendation requirements of IPTV video were analyzed,the IPTV video user portrait with “virtual video users” was structured,a personalized recommendation system was built which included a batch data analysis system and a streaming architecture of personalized recommendation engine.Experimental results show that it is a useful attempt in enhancing the use experience of IPTV users.